Safety Risk Assessment Model for Bridge Construction - Hartono, Widi; Kristiawan, Stefanus A.; Handayani, Dewi; Sutopo, Wahyudi (Salehan Institute of Higher Education, 2025)
In Indonesia, construction accidents have occurred during the construction of bridges and elevated roads, peaking in 2017. The lifting of girder beams has failed in several construction projects, and the formwork has failed during pier construction. The reasons for these work accidents are human and equipment factors, which caused material losses and loss of life. A risk assessment model for bridge construction work accidents in construction projects is proposed in this paper, with the work breakdown structure (WBS), risk breakdown structure (RBS), analytic hierarchy process (AHP), and rating being integrated to assess the risk of bridge construction work accidents. This model is expected to improve safety in bridge construction by providing effective safety planning, especially in the accident risk assessment process. The study results indicate that the WBS and RBS can outline and explain the identification of construction safety risks for bridges and provide insight into the interrelationship of construction phases and the potential risks. The relationship between the WBS and RBS is created in the form of a coupling matrix, and we identify the potential risky activities at each phase and the corresponding construction phases. The AHP can be used to calculate the weights and priorities of the WBS and analyze the magnitude of the risk index for its related risky activities; then, the rating method can be used to analyze the risk index. Girder and diaphragm installation work involves a high risk of workers falling during the erection of girders. Doi: 10.28991/CEJ-2025-011-01-010 Full Text: PDF